Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Yeah, need help solving this one...

A function is given below. Determine the average rate of change of the function between x = 1 and x = 7.

g(x)= 3 + 1/2x

share|cite|improve this question
Compute $g(7)-g(1)\over 7-1$. – David Mitra Sep 24 '12 at 21:19
up vote 1 down vote accepted

Suppose that $g(1)=4$ and $g(7)=2$. (Neither of these is true, but I’ll use them to illustrate what’s going on.) Then the function has changed by $2-4=-2$ units between $x=1$ and $x=7$. That’s $-2$ units of change in $g$ while $x$ changed by $7-1=6$ units, so on average $g$ changed by $\frac{-2}6=-\frac13$ of a unit every time $x$ increased by $1$ unit. That is, the average rate of change was $-\frac13$ (units change in $g$ per $1$-unit change in $x$).

Now you try it with the actual values of $g(1)$ and $g(7)$.

share|cite|improve this answer

A particle is travelling in a straight line. Suppose that $f(t)$ is the displacement (position) of the particle at time $x$. Then the average velocity from time $t=a$ to time $t=b$ is $\dfrac{f(b)-f(a)}{b-a}$. It is the change in displacement, divided by the time it took. In other words, it is the average rate of change of displacement.

If the population of a country at time $t$ is $P(t)$, then the average rate of change in population from time $t=a$ to time $t=b$ is the change in population, divided by the time it took. This is $\dfrac{P(b)-P(a)}{b-a}$.

share|cite|improve this answer

Saying what others have said a tiny bit differently: By definition the average rate of change of a function $g$ over the interval $[a,b]$ is $$ \frac{g(b) - g(a)}{b-a}. $$ In you case $g(x) = 3 + \frac{1}{2}x$ and $a = 1$ and $b = 7$. So you have

$$ \begin{align} \frac{g(7) - g(3)}{7-3} &= \frac{3 + \frac{1}{2}\cdot 7 - (3 + \frac{1}{2}\cdot 3)}{7 - 3} \\ &= \dots \end{align} $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.